Gambaran hasil pemeriksaan fungsi hati pada anak dengan infeksi dengue periode Januari 2011-Oktober 2016 di RSUP Prof. Dr. R. D. Kandou Manado - Saudo, Rindah M.; Rampengan, Novie H.; Mandei, Jose M. (Universitas Sam Ratulangi, 2016)
Abstract : Dengue infection still one of the global health problem. Hepatic dysfunction is common in dengue infection and the spectrum of liver dysfunction in children with dengue infection is wide and has been associated with disease severity. Hepatic dysfunction can be measured with aminotransferase levels. Significant rise of aminotransferase level helps in recognition of severe form of dengue infection. This study aimed to obtain the profile of aminotransferase levels of children diagnosed with dengue infection. This was a descriptive retrospective study using medical record data of patients in Pediatrics Department Prof. Dr. R.D. Kandou Hospital Manado. There were 432 patients with dengue infection during the period 2011-2016. Patients performed liver function test were 222 patients, however, only 183 patients that meet the inclusion criteria. All cases were grouped into Dengue Fever (DF), Dengue hemorrhagic fever (DHF) and Dengue shock syndrome (DSS) according to WHO criteria. Most patient diagnosed with DSS. Aminotransferase levels rise more significant in DSS and DHF group compared to DF group. AST was elevated more than ALT.Keywords: dengue infection, children, liver function, AST, ALTÂ Abstrak: Infeksi dengue masih merupakan masalah kesehatan global. Disfungsi hati umum ditemukan pada infeksi dengue dan spektrum disfungsi hati pada anak dengan infeksi dengue luas dan berkaitan dengan keparahan penyakit. Disfungsi hati dapat diukur dengan kadar aminotransferase. Peningkatan signifikan kadar enzim transaminase dapat membantu mengenali infeksi berat virus dengue. Penelitian ini bertujuan untuk mengetahui gambaran hasil pemeriksaan fungsi hati pada anak dengan infeksi dengue. Penelitian ini adalah penelitian deskritif retrospektif dengan menggunakan data rekam medik pasien di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado. Sebanyak 432 pasien infeksi virus dengue periode 2011-2016 dan yang diperiksa fungsi hati sebanyak 222 pasien, namun hanya 183 pasien yang memenuhi kriteri inklusi. Semua kasus dikelompokkan menjadi Demam Dengue (DD), Demam berdarah dengue (DBD), dan Sindroma Syok Dengue (SSD). Pasien terbanyak adalah pasien SSD. Peningkatan kadar enzim aminotransferase lebih signifikan pada kelompok SSD dan DBD dibandingkan DD. SGOT meningkat lebih tinggi dibandingkan SGPT. Kata kunci: infeksi dengue, anak, fungsi hati, AST, ALT